Numerical study of gas production from marine hydrate formations considering soil compression and hydrate dissociation due to depressurization. (April 2019) - Sun, Xiang; Luo, Hao; Luo, Tingting; Song, Yongchen; Li, Yanghui
Abstract: Depressurization is considered a key method for extracting natural gas from marine gas hydrates in the petroleum industry. Permeability is one of the significant factors impacting gas production. Low-permeability formations tend to be related to low gas production. The effective permeability of hydrate-bearing sediments depends on both porosity and hydrate saturation. Because the sediments bear external loads during depressurization, analyses of gas production from hydrate should consider the volume change in the formation in response to earth stress. In this paper, several parametric analyses were conducted using a fully coupled thermo-hydro-chemo-mechanical (THCM) model to analyze gas production during depressurization when considering soil compression. The simulation results show that boundary effects exist when small models are used for long-term simulations. Compression may result in a lower effective permeability in the hydrate dissociated zone than that in the hydrate undissociated zone. The gas flow rate is affected by the difference in the effective permeability between the hydrate dissociated zone and the hydrate undissociated zone. Meanwhile, lower downhole pressure leads to more serious soil compression, which may not benefit gas production. Highlights: The effects of volume contraction due to soil compression on the gas production is significant. There may be an optimized hydrate saturation for gas production. The effective permeability in the hydrate dissociated zone may be lower than undissociated. The effect of decreasing downhole pressure on increasing gas production rate may be limited.